Discharge coefficient of side weirs in curved channels - Agaccioglu, Hayrullah; Emiroglu, M. Emin; Kaya, Nihat (Ice Publishing, 2012)
Side weirs are flow diversion devices commonly used in irrigation, land drainage and urban sewage systems. It is essential for hydraulic and environmental engineers involved in the design of side weirs to predict the discharge coefficient correctly. The aim of this study is to present an accurate equation for discharge coefficients along the bend of sharp-crested rectangular side weirs based on a total of 1504 experimental runs. The discharge coefficient of the rectangular side weir along the bend depends on the dimensionless parameters of Froude number in the main channel F-1, the angle of bend curvature alpha, the ratio of weir length to main channel width L/b, the ratio of weir length to radius of main channel centreline L/r(c) and the ratio of weir height to upstream flow depth p/h(1). In particular, the variables L/rc and p/h(1) are not seen in any equation for a rectangular side weir located on a curved channel. However, it was found that these dimensionless parameters were significantly important for the overflow rate. Moreover, the equation in the literature needs interpolation in order to obtain the discharge coefficient for different L/b and alpha values. Therefore, a reliable equation containing all dimensionless parameters for calculating the discharge coefficient was introduced.
Keywords: hydraulics & hydrodynamics; river engineering; waterways & canals